EDUCATIONAL INTERFACES AND DIDACTIC INNOVATION IN THE DESIGN OF E-LEARNING SPACES - Pereira Nicácio, Jailton; Trajano de Souza, Joseilson; Trajano de Souza, Josenete; Lisboa Galvão do Nascimento, Jonatha; Modesto Favacho, Kelsin; Helena de Paula Modesto Favacho, Lucia; Santos do Nascimento, Marielza; Campos Rodrigues, Mayara; Ricardo Pereira Accioly, Sérgio (Revista Gênero e Interdisciplinaridade, 2026)
The careful incorporation of digital technologies into educational processes redefines the design of e-learning spaces, shifting the focus from a simple transposition of content to interactive experiences that integrate multiple languages. By articulating didactic innovation and pedagogical design, the configuration of virtual environments involves decisions that directly affect student motivation and retention. Interactivity, usability, and coherence between objectives and strategies emerge as determining factors for consistent and sustainable educational practices. Based on bibliographic research, this study aims to understand the relationships between pedagogical design, interactivity, and didactic innovation in the context of e-learning. The focus includes works that discuss the role of collaborative platforms, the applicability of engagement metrics, and the incorporation of multimedia resources in knowledge mediation. The aim is to identify how these dimensions, when combined in a planned manner, can generate immersive educational experiences, supported by a formative logic centered on the learner’s protagonism and the effectiveness of interactions. The analysis is organized around three interdependent axes: the visual architecture of the platforms, teacher mediation strategies, and the personalization of training pathways. This approach allows us to understand how to design choices and active methodologies, when combined with appropriate technological resources, expand opportunities for networked learning. Ultimately, the study highlights implications for institutional policies and pedagogical practices committed to the quality and social relevance of digital education.